2014
DOI: 10.1007/s12265-013-9539-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood Outgrowth Endothelial Cells Alter Remodeling of Completely Biological Engineered Grafts Implanted into the Sheep Femoral Artery

Abstract: Hemocompatibility of tissue-engineered vascular grafts remains a major hurdle to clinical utility for small-diameter grafts. Here we assessed the feasibility of using autologous blood outgrowth endothelial cells to create an endothelium via lumenal seeding on completely biological, decellularized engineered allografts prior to implantation in the sheep femoral artery. The 4-mm-diameter, 2- to 3-cm-long grafts were fabricated from fibrin gel remodeled into an aligned tissue tube in vitro by ovine dermal fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Their findings were that the cell-seeded grafts had a better resolution than the cell-free ones, even if they concluded that the administration of antiplatelet drugs could have altered the outcomes. In comparison, our findings involve implants without antiplatelet therapy, strengthening the results of the study by Meier et al [2014]. Our study does have limitations, however, concerning the number of animals involved and the peculiarity of the chimeric model in which the immune-suppressive drug could have influenced the outcome.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Their findings were that the cell-seeded grafts had a better resolution than the cell-free ones, even if they concluded that the administration of antiplatelet drugs could have altered the outcomes. In comparison, our findings involve implants without antiplatelet therapy, strengthening the results of the study by Meier et al [2014]. Our study does have limitations, however, concerning the number of animals involved and the peculiarity of the chimeric model in which the immune-suppressive drug could have influenced the outcome.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, there is a contradiction, on the one hand, the seeded endothelial cells are lost within a few days, and on the other, it seems that cell-free implants have a worse resolution in the long term than seeded ones. Very recently, Meier et al [2014] investigated the in vivo implantation in ovine femoral arteries of fibrin-gel decellularized engineered vessels with no cells or with blood-outgrowth endothelial cell seeding. Their findings were that the cell-seeded grafts had a better resolution than the cell-free ones, even if they concluded that the administration of antiplatelet drugs could have altered the outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We report elsewhere studies of these grafts preseeded with endothelial cells. 33 It is well known that predominate circumferential alignment of the media in the native artery confers its unique biomechanical properties. 34 The method used to create the fibrin-based TEVG-cell-induced gel compaction on a nonadhesive mandrel, which allows for axial shortening, but with mechanically constrained circumferential and radial compaction-yields strong circumferential alignment.…”
mentioning
confidence: 99%